The impact of Orem self-care theory on health behaviours modification among myocardial infarction patients: a quasi-experimental study - Sultan, Amir; Khanum, Sabiha; Naz, Najma (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the effectiveness of Orem self-care theory intervention on health behaviours modification among myocardial infarction patients. Method: The quasi-experimental study was conducted at the Cardiology Ward of Saidu Group of Teaching Hospital, Swat, Khyber Pukhtankhwa, Pakistan, from August to November 2022, and comprised patients of either gender aged 50-70 years who were admitted with diagnosed myocardial infarction and spent at least four days at the cardiac unit who were found eligible to be enrolled by on-duty doctors. The patients were divided into intervention group A and control group B through systemic sampling technique. Pre-test was conducted within 48 hours of admission in both the groups. The intervention in group A, based on the Orem self-care theory, consisted of two sessions of 30 minutes. Those in group B received routine care. The post-test was conducted after eight weeks. Data was collected through a valid and reliable health behaviours checklist. Data was analysed using SPSS 22. Results: Of the 60 patients, 30(50%) were in group A; 15(50%) males and 15(50%) females with mean age 61.53±5.5 years. The other 30(50%) patients were in group B; 16(53%) females and 14(47%) males with mean age 60.7±5.3 years. Intragroup difference in post-intervention overall score was significant (p<0.05), but group A showed more improvement compared to group B (p<0.05). Conclusion: Orem self-care theory intervention could be more beneficial to myocardial infarction patients. Key Words: Myocardial infarction, Coronary artery diseases, Health-related quality of life, Lifestyle behaviour, Pakistan, Lifestyle modification.